2000
DOI: 10.1017/s0007114500000040
|View full text |Cite
|
Sign up to set email alerts
|

Total fluoride intake and urinary excretion in 4–year–old Iranian children residing in low-fluoride areas

Abstract: Knowledge of levels of fluoride ingestion and excretion is important in planning optimum fluoride therapy for young children. In previous literature, it has been assumed that only about one-third of ingested fluoride is excreted in young children. The aims of the present study were (a) to measure total fluoride intake, urinary fluoride excretion and fluoride balance, and (b) to investigate the effect of air temperature on fluoride intake and urinary fluoride excretion, in young children. Children (4 years old)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 35 publications
4
45
2
Order By: Relevance
“…The amount of urinary fluoride excreted reflects the amount of fluoride ingested, and elimination of absorbed fluoride occurs mainly via kidney [23]. As reported in literature, the urinary excretion of fluoride (age group 3-6 years) is 32-80% of total fluoride intake [24][25][26]. Fluoride, in faeces, is that part which was never absorbed [27].…”
Section: Metabolism Of Fluoridementioning
confidence: 99%
See 1 more Smart Citation
“…The amount of urinary fluoride excreted reflects the amount of fluoride ingested, and elimination of absorbed fluoride occurs mainly via kidney [23]. As reported in literature, the urinary excretion of fluoride (age group 3-6 years) is 32-80% of total fluoride intake [24][25][26]. Fluoride, in faeces, is that part which was never absorbed [27].…”
Section: Metabolism Of Fluoridementioning
confidence: 99%
“…Fluoridated drinking water was found positively associated with cancer of oral cavity and pharynx, colon and rectum, hepato-biliary and urinary organs [39]. Human beings are protected from the adverse effect of high fluoride ingestion by the dietary habits as well as by various functions carried out by their organs, as 40-60% of fluoride ingested daily is excreted by kidneys through urine [26,40]. Calcium and magnesium form insoluble complexes with fluoride anion and multivalent cations in the small intestine and decrease the uptake of fluoride into bones and teeth significantly [40,41].…”
Section: Health Effectsmentioning
confidence: 99%
“…A report from WHO [23] has reported that absorbed fluoride is excreted mainly through kidney [23]. It has been documented that the urinary excretion of fluoride (age group 3-6 years) is 32-80% of total fluoride intake [26][27][28]. The fluoride excreted in faeces, is that fraction which is not absorbed in the body [29].…”
Section: Resultsmentioning
confidence: 99%
“…18,19 In brief, the districts chosen were a big city (Shiraz) and a provincial town (Darab) together with its surrounding rural area. 18,19 In brief, the districts chosen were a big city (Shiraz) and a provincial town (Darab) together with its surrounding rural area.…”
Section: Methodsmentioning
confidence: 99%
“…19 In brief, validity was estimated by (i) calculating the physical activity level (PAL), and (ii) comparing the energy intakes of the children with those obtained in other studies and reference values. 19 In brief, validity was estimated by (i) calculating the physical activity level (PAL), and (ii) comparing the energy intakes of the children with those obtained in other studies and reference values.…”
Section: Methodsmentioning
confidence: 99%